2016
DOI: 10.1039/c6ta02715f
|View full text |Cite
|
Sign up to set email alerts
|

The interaction of molecular oxygen on LaO terminated surfaces of La2NiO4

Abstract: Rare-earth metal oxides with perovskite-type crystal structures are under consideration for use as air electrode materials for intermediate to high temperature electrochemical device applications.The surface chemistry of these materials plays a critical role in determining the kinetics of oxygen reduction and exchange reactions. Among various perovskite-structured oxides, certain members of the Ruddlesden-Popper series, e.g. La2NiO4, have been identified as significantly active for surface oxygen interaction. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
70
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 60 publications
(81 citation statements)
references
References 58 publications
(41 reference statements)
10
70
1
Order By: Relevance
“…Since the partial SrO termination is expected to dominate the surface under SOFC operating conditions, we examine its possible relevance in the oxygen reduction reaction. For assessing the catalytic activity of SOFC cathodes in the oxygen reduction reaction (ORR), several different factors play a role, such as the coverage of adsorbed oxygen and its dissociation barrier, but also the oxygen vacancy concentration near the surface and the mobility of these vacancies [17,29,[34][35][36]. While we have not studied these aspects yet in detail for our proposed partial MnO 2 /LaO/SrO terminations, we would like to point out that such terminations may have special properties in the context of the ORR, based on the results of previous studies of Merkle et al [33] and Mastrivkov et al [29].…”
Section: Possible Role Of the Partial Sro And Lao Terminations In mentioning
confidence: 99%
“…Since the partial SrO termination is expected to dominate the surface under SOFC operating conditions, we examine its possible relevance in the oxygen reduction reaction. For assessing the catalytic activity of SOFC cathodes in the oxygen reduction reaction (ORR), several different factors play a role, such as the coverage of adsorbed oxygen and its dissociation barrier, but also the oxygen vacancy concentration near the surface and the mobility of these vacancies [17,29,[34][35][36]. While we have not studied these aspects yet in detail for our proposed partial MnO 2 /LaO/SrO terminations, we would like to point out that such terminations may have special properties in the context of the ORR, based on the results of previous studies of Merkle et al [33] and Mastrivkov et al [29].…”
Section: Possible Role Of the Partial Sro And Lao Terminations In mentioning
confidence: 99%
“…23 This is especially true for perovskite lattices with alkaline and earth alkaline metals on the A-site, e.g., Sr, Ba, etc., while different catalytic mechanism based on d-electron occupancy was proposed for perovskites with rare earth elements on the A-site, e.g., La, Pr, etc. 24 The electronic properties in the vicinity of surface oxygen vacancies of SrTiO 3 have shown that those vacancies are not simply spatial voids but are regions in space characterized with high electron density. 20 As the molecular oxygen activation and dissociation in an electrophilic reaction, surface oxygen vacancies would be the preferred surface active sites.…”
Section: Introductionmentioning
confidence: 99%
“…5a), in agreement with hybrid LCAO calculations, 55 plane wave GGA calculations 19 and atomic O adsorption on the LaO termination of La 2 NiO 4 . 56 The adsorption energy depends strongly on the Mn oxidation state (see Fig. 7a below) and can reach À4.3 eV.…”
Section: Atomic and Molecular Oxygen Adsorptionmentioning
confidence: 99%